Ductile iron pipes, fittings and accessories. Requirements and test methods for organic linings of ductile iron pipes and fittings. Thermoplastic Acid Modified Polyolefin (TMPO) lining of pipes Part 2, (18th November 2020) - British Standards Institution,
No abstract available